Neuronal Dopamine Subpopulations Maintained in Hypothalamic Slice Explant Cultures Exhibit Distinct Tyrosine Hydroxylase mRNA Turnover Rates - Maurer, Jennifer A. (J Neurosci, 1997)
Changes in mRNA stability have been shown to regulate critical intracellular processes. In this investigation, we studied tyrosine hydroxylase (TH) mRNA turnover in functionally and anatomically distinct dopaminergic (DA) populations of the rat hypothalamus. To this end, long-term slice explant cultures from postnatal, preoptic area/hypothalami, containing three anatomically discrete DA populations, were generated and maintained under defined conditions. The organotypic cultures were treated with the transcription inhibitors 5,6-dichloro-1-D-ribofuranosylbenzimidazole or actinomycin D and processed for in situ hybridization histochemistry. Relative TH mRNA content per cell was quantitated. Single-cell analysis showed marked differences in basal TH mRNA turnover rates between DA neuronal populations. Anterior and midhypothalamic DA neurons exhibited half-time turnovers of 9–12 and 11–23 hr, respectively. In contrast, in the caudal hypothalamus, DA neurons of the arcuate nucleus had a significantly lower baseline level and more rapid turnover (6–7 hr) of TH mRNA. This investigation shows that basal turnover of a phenotypic mRNA, TH mRNA in DA neurons, is not an intrinsic property of the phenotypic marker. Furthermore, we found that destabilization of TH mRNA in the caudal hypothalamus corresponds to the known rhythmic output displayed by arcuate DA cells and, as such, may be critical for normal function of this population. We propose that intrinsic differences in the post-transcriptional regulation of TH permits neuronal subpopulations, which subserve different physiological functions, an additional mechanism to control DA biosynthesis in response to their unique needs.